A case of toxoplasmic encephalitis in a patient on cancer chemotherapy in Uganda - Mitala, Yekosani; Atwine, Raymond; Birungi, Abraham; Ambaru, Jacinta; Kuraishi, Baluku; Sekitene, Semei; Nuwagira, Edwin (African Journals Online (AJOL), 2025)
Background: Reactivation of central nervous system (CNS) toxoplasmosis can be caused by immunosuppression (ISS) of any kind. However, anti-cancer chemotherapy combined with human immunodeficiency virus (HIV) induced ISS results in an atypical presentation that is fatal. Case presentation: A 46 years old man with a well-controlled infection of the human immunodeficiency virus presented with generalized tonic-clonic seizures following the second dose of anti-cancer chemotherapy for esophageal cancer. His brain's computerized tomography (CT) scan showed enlarged ventricles with no space-occupying lesions. Cerebrospinal fluid (CSF) smears stained with hematoxylin and eosin (H&E) revealed numerous bradyzoites and tachyzoites consistent with central nervous system toxoplasmosis. Conclusion: With a double burden of cancer and Human immunodeficiency virus (HIV) infection in low-income countries, this case raises awareness about the atypical presentation of CNS toxoplasmosis reactivation among patients on cancer chemotherapy.